Specific Expression of DR5 Promoter in Rice Roots Using a tCUP Derived Promoter-Reporter System - Zhou, Jie; Yu, Feibo; Wang, Xuming; Yang, Yong; Yu, Chulang; Liu, Hongjia; Cheng, Ye; Yan, Chengqi; Chen, Jianping (PLOS ONE, 2014)
Variation of transgene expression caused by either position effect at the insertion site or the promoter/enhancer elements employed for the expression of selectable marker genes has complicated phenotype characterization and caused misinterpretation. We have developed a reporter system in rice to analyze the influence of vector configuration, spacer and selectable marker gene promoter on the expression of the promoterless GUS reporter and DR5 promoter. Our results indicate that a spacer inserted between the reversed 35S promoter and the GUS reporter could reduce leaky expression of the reporter but was unable to block the nonspecific expression of DR5::GUS. Stacking the selectable marker unit in head to tail with the GUS reporter aided the gene specific expression of the GUS reporter under the DR5 promoter even when the 35S promoter is used for expression of the selectable marker. Compared to 35S under this configuration, a quick and distinctive expression of DR5::GUS was observed in the root cap, quiescent center and xylem cells in the root apical meristem by using the tCUP derived promoter (tCUP1) for selection, that is similar to the pattern obtained by a sensitive DR5 variant (DR5rev) in Arabidopsis. These data suggest a conserved property of the tCUP promoter in preventing enhancer-promoter interactions in rice as it does in Arabidopsis, and also demonstrate that an analogous distal auxin maximum exists in roots of rice. Therefore, the tCUP promoter based selection system provides a new strategy for specific expression of transgenes in rice.